Neglected fracture of bilateral mandibular corpus: A case report - Wayan HS. Sandi; Wenny Yulvie; Yudy A. Utomo; Vera Julia; Lilies D. Sulistyani (Journal of Dentomaxillofacial Science, 2021)
Objective: This paper aimed to report the management of neglected bilateral mandibular corpus fracture with open reduction and fixation technique. Method: A 38-year-old male patient was referred to Dr. Cipto Mangunkusumo Hospital with chief complaints can not close the mouth and chewing food properly. The patient had a history of injured in motor vehicle accidents, 3 months ago. Extra oral examination showed facial asymmetry, while in ntra oral examination revealed anterior open bite malocclusion. In orthopantomogram (OPG) image, fracture lines in bilateral mandibular corpus were seen. Results: The fractures were managed with Open Reduction Internal Fixation (ORIF) using reconstruction plates to reestablished the occlusion and facial asymmetry. Postoperative evaluation showed good occlusion and facial symmetrical without injured the mental nerve. Conclusion: Early and proper management of bilateral mandible corpus fracture will provide the optimum result. Refracturing the neglected bilateral mandibular corpus is treatment choice in order to restore the mastication and aesthetic function.